Right-side inguinal canal endometriosis at ultrasound: A case report - Abolfazl Mehdizadeh; Shahla Chaichian; Shahla Mirgaloybayat; Samaneh Rokhgireh; Kobra Tahermanesh; Maryam Kadivar; Farahnaz Farzaneh (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: The first case of inguinal endometriosis was described by Cullen. Endometriosis in the round ligament could be in the pelvic or inguinal area and is a rare disease occurring in 0.6% of women. Women with inguinal endometriosis have a painful inguinal mass during menstrual cycles and they mostly have a history of surgery. The right side is more commonly involved in inguinal endometriosis than the left side (90-94%). A history of gynecologic or abdominal surgery is common in women with inguinal endometriosis. Case presentation: In our case, a 39-yr-old virgin woman presented with localized pain in the right inguinal that had been present for 4 yr. She did not have any history of previous surgery, and abdominal ultrasonography showed a hypoechoic mass with minimal vascularity. Inguinal endometriosis was correctly diagnosed by two expert radiologists preoperatively, and she underwent laparoscopic surgery. Conclusion: Considering inguinal endometriosis in the differential diagnosis of women with inguinal masses is important, even if there is no history of gynecologic or abdominal surgery.